Indoor and outdoor relationships of particle with different sizes in an apartment in Hanoi: mass concentration and respiratory dose estimation - Ha, Vo Thi Le; Anh, Van Dieu; Hien, Nguyen Thi Thu; Dung, Nghiem Trung; Simada, Yoko; Yoneda, Minoru (Vietnam Journal of Science and Technology, 2020)
This paper presents data on the size characterization concentration of PM0.1, PM0.5, PM1, PM2.5, PM10, TSP in indoor and outdoor air of a residential apartment in two seasons (winter and summer) in Hanoi, Vietnam. These particles with different sizes were taken by 5 stage impactors (Nano sampler 3182, KINOMAX). Daily average concentrations of coarse particles (PM10) and fine particles (PM2.5) indoors and outdoors exceeded the WHO recommended values. In winter, the concentrations of PM0.5, PM1, PM2.5 and PM10, TSP are higher than in summer. However, concentrations of PM0.1 (NP) remains negligible change between two seasons. The indoor NP accounts about 17% and 8 % of fine particle (PM2.5) and 12 % and 7% of coarse particle (PM10) in winter and summer, respectively.  The indoor fraction for small sizes (NP, PM0.5, PM1 and PM2.5) have better infiltration than coarse sizes (PM10  and TSP), except for NP in summer. Moderate correlation between wind speed  (Ws) and PM concentration are found, whereas precipitation (Pr), Relative humidity (RH) and temperature (T) correlate with concentration with different sizes are determined. Strong correlations between particles with different sizes are also found in indoors and outdoors (r = 0.73-0.98). Household activities like cooking, cleaning and vacuum cleaner are attributed to elevate the indoor NP. The Monte Carlo simulation shows that highest estimated dose is observed in the age group (over 60 years) and age group (0-3 years) suffers the lowest dose, which has implications in the adverse health effects for sensitive groups. Sensitive analysis find the concentration of particles to be the most influencing factor on inhalation dose estimation